2017
DOI: 10.1016/j.jad.2017.05.048
|View full text |Cite
|
Sign up to set email alerts
|

Emotional blunting with antidepressant treatments: A survey among depressed patients

Abstract: Emotional blunting is reported by nearly half of depressed patients on antidepressants. It appears to be common to all monoaminergic antidepressants. The OQESA scores are highly correlated with HAD depression score; emotional blunting cannot be described simply as a side-effect of antidepressants, but also as a symptom of depression. A higher degree of emotional blunting is associated with a poorer quality of remission. The OQESA scale allows the detection of this phenomenon.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
86
0
6

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 129 publications
(97 citation statements)
references
References 10 publications
5
86
0
6
Order By: Relevance
“…Similar to our study, a previous study found patients who had taken antidepressants in the past had more favorable attitudes toward pharmacologic treatment . Furthermore, the side effect from pharmacologic treatment of emotional blunting reported by the TTP patients is a commonly reported side effect of selective serotonin reuptake inhibitors . Additionally, fears related to pharmacologic treatment are similar to previous studies done with participants with conditions other than TTP.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Similar to our study, a previous study found patients who had taken antidepressants in the past had more favorable attitudes toward pharmacologic treatment . Furthermore, the side effect from pharmacologic treatment of emotional blunting reported by the TTP patients is a commonly reported side effect of selective serotonin reuptake inhibitors . Additionally, fears related to pharmacologic treatment are similar to previous studies done with participants with conditions other than TTP.…”
Section: Discussionsupporting
confidence: 90%
“…19 Furthermore, the side effect from pharmacologic treatment of emotional blunting reported by the TTP patients is a commonly reported side effect of selective serotonin reuptake inhibitors. 37 Additionally, fears related to pharmacologic treatment are similar to previous studies done with participants with conditions other than TTP. A focus group of Black women, without TTP, with major depressive disorder, described fears of pharmacologic treatment related to unknown side effects, addiction, and dependence on a medication.…”
Section: Discussionsupporting
confidence: 75%
“…Nevertheless, all analyses included age, sex, and years of education as covariates, as these factors can affect the relationship between depression status and functional outcomes (Evans et al., ; Mackin & Areán, ). Previous research has indicated that use of selective serotonin/norepinephrine reuptake inhibitors (SSRIs/SNRIs) can enhance flattened emotional experience/perception (i.e., emotional blunting) (Goodwin, Price, De Bodinat, & Laredo, ); a symptom that could affect social perception in the ACS. Eighteen participants in the lifetime MDD group were taking an SSRI/SNRI (current MDD n = 9, remitted MDD n = 9), however, regression analyses indicated that SSRI/SNRI use was not related to ACS performance or FAST total score ( Ps > 0.05).…”
Section: Methodsmentioning
confidence: 99%
“…A potential detrimental manifestation of long-term treatment with antidepressants may be the emotional blunting phenomenon (vide infra) or otherwise "depressogenic" phenomena [33][34][35][36].…”
Section: Accepted Manuscriptmentioning
confidence: 99%